PERAN HUKUM BISNIS DALAM MENCIPTAKAN IKLIM USAHA YANG SEHAT DAN BERKELANJUTAN - Annisa Rizki Ananda; Intan Ramadhani; Sri Handayani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Business law plays a strategic role in creating a healthy and sustainable business climate amid globalization and digital economic transformation. This study aims to analyze the role of business law in regulating, protecting, and promoting sustainable business activities in Indonesia. The research employs a normative juridical method using statute and conceptual approaches, with secondary data derived from laws and regulations such as Law No. 5 of 1999, Law No. 8 of 1999, and Law No. 11 of 2020, as well as official reports from the Central Bureau of Statistics (BPS) and the Business Competition Supervisory Commission (KPPU). The results indicate that business law contributes to legal certainty, promotes fair competition, and ensures the protection of consumers and the environment. Policies such as the risk-based licensing system through the Online Single Submission (OSS) platform facilitate business processes and enhance investment. However, the implementation of business law still faces several challenges, including weak law enforcement, regulatory disharmony, and low legal awareness among business actors, particularly micro, small, and medium enterprises (MSMEs). Therefore, regulatory harmonization, stronger law enforcement, and increased legal education for business actors are necessary to establish a fair, competitive, and sustainable business environment in Indonesia.